지구과학에서 구성주의적 사고력 신장을 위한 수업전략의 효과 - 김수진; 김찬기; 김상달; Kim, Soo-Jin; Kim, Chan-Ki; Kim, Sang-Dal (대한지구과학교육학회지, 2010)
This study is aiming to structure progressive instructional strategy for development of constructivist-thinking into the beginning stage, developmental stage, and advanced stage, then organize multiple choice, completion, descriptive, and essay problems to be suitable for each stage of the strategy, and finally, to evaluate what effects this instructional strategy has on the students' academic achievements and enhancement of their scientific essay writing skills. The results of the study are as follows. First, lessons applying the strategy for developing constructivist-thinking were more effective in enhancing student' academic achievement than the text book-oriented lecture type lessons. In changes in academic achievement, the test group, for both high and low levels, displayed a higher average than the control group, however, changes in the high level was not statistically significant and changes in the low level students were found to be statistically significant. Second, scientific essay writing skills were found to be effective in all levels of the test group and the averages in both high and low groups of the test group were higher than those of the control group and were also found to be statistically significant.